Comparative Evaluation of Self and Cross-Grafting Combinations in Tomato Plants (Journal of Agriculture and Biology, 2025)
Tomato production encounters various challenges due to a range of abiotic and biotic stresses. The increased consumption demand of tomato in terms of quality and production needs better strategies to alleviate the effects of different climatic stresses. These stresses can be mitigated by grafting which is an innovative technique in tomato. The present study highlights the effects of tomato grafting by using various scion-rootstock combinations on tomato growth and yield. Three tomato cultivars viz. Roma, Bush beefsteak, and Bushel Boy) were self and cross grafted via cleft grafting method in Completely Randomized Design with three replications. The highest grafting success was observed in cross grafted combination of Bush beefsteak on the Bushel Boy as well as on Roma rootstocks. The taller plants with earlier flowering and fruiting were noticed from the non-grafted plants in comparison to the plants that were grafted. However, maximum fruits per plant were observed from grafted combinations where scion or rootstock of the Bushel Boy was grafted with Bush Beefsteak. Maximum fruit diameter, weight of fruit and yield of fruit per plant was also observed from same grafted combination of Bush Beefsteak grafted on the rootstock of Bushel Boy. It is concluded that scion-rootstock combinations had significant effects on yield related parameters of Tomato. Bush Beefsteak and Bushel Boy proved to have best scion-rootstock combination. Non-grafted plants had earlier flowering and fruiting while grafted plants produced maximum fruits as well as yield per plant in comparison to self and without grafting plants. The Bush Beefsteak and Bushel Boy outperformed.